PEMBENTUKAN KARAKTER BERBASIS PENDIDIKAN PESANTREN: Studi di Pondok Pesantren Tradisional dan Modern di Kabupaten Ponorogo - Makmun, H.A. Rodli (IAIN Ponorogo, 2014)
Abstract: Character education meant as value education, ethic kindness education,moral education, which its aim to developingparticipant ability in order to give decisionof good-bad, looking after of goodness, and realize that kindliness in everyday life obligingly. In consequence character education as psychologically include dimension;moral reasoning, moral feeling, and moral of behavior.Character education inIslamic Boarding School conducted integrally with educationprocess in Islamic Boarding School. Character education do not become separate teaching item. It is true there isspecial subject of behavior, namely baninlilakhla, al-nawbawiakhlaq, makhfudhat, interpretation, hadits, and so on, but that study havegeneral nature to add knowledge of santri, forming patterned thinking and santri behavior. Santricharacter formed by the sake of Allah, serving, respecting, down to earth, modestly, self-serving, and free in Islamic Boarding School community. IslamicBoarding School design inuring pattern during 24 hour in Islamic Boarding School.Santricharacter of traditional Islamic Boarding Schoolturn to yellow bookfrom studyingand habituation in order toobeyIslamic Boarding School orders Â Ø³Ø±Ø§Ø¯ÙÙ Ø§ .Ø©ÙÙÙØ³ÙØ§Ù ØØ©Ø«ÙØ¯ØÙ ÙØ¯ÙÙÙØªÙØ§ Ø·Ù ÙÙØ§Ù ØØ©ÙÙØªÙ Ø® ÙÙØ§Ø¸ Ø©Ø«ÙØ§Ø« Ø¹ÙØ§ÙÙØ§ ÙÙ Ø§ÙÙØ¯Ù Ø©ÙÙØ®Ø§Ø¯ÙØ§ Ø©ÙÙ ÙØ§Ø³ÙØ¥Ø§ Ø³Ø±Ø§Ø¯ÙÙ Ø§Â Ø©Ø«ÙØ¯ÙØØ§ ÙØ¯ÙÙ Ø©ÙÙØ®Ø§Ø¯ Ø©Ø³Ø±Ø¯Ù Ø©ÙÙ ÙØ§Ø³ÙØ¥Ø§ ÙØ¯ÙÙØ§ Ø±Ø§Ø¯ ÙØ§Ø«ÙÙ Ø§ ÙÙØ¨Ø³ ÙÙØ¹ Ø©Ø´ÙÙÙÙ Ø¤Ø¬Ø¤ÙØ¤Ù ÙÙ Ø©ÙÙØ®Ø§Ø¯ÙØ§ Ø©ÙÙ ÙØ§Ø³ÙØ¥Ø§Â ØÙØºÙÙØ³ ÙÙØ§Ù Ø©ÙÙØ®Ø§Ø¯ÙØ§ Ø©ÙÙ ÙØ§Ø³ÙØ¥Ø§ Ø³Ø±Ø§Ø¯ÙÙ Ø§Ù ØØ©Ø«ÙØ¯ÙØØ§ Ø©Ø±Ø¬ÙØØ§ ÙÙØ¯ÙÙØ¨ ÙØ§ÙÙ ÙØ£ ÙÙØ ÙÙ ÙÙÙ Ø©Ø´ÙÙÙÙ ÙØ¯ÙÙÙØªÙØ§.ÙØ§ÙÙ Ø¥ ÙØ¢ ÙÙØ¯ÙÙØ¨ Ø©ÙÙØ®Ø§Ø¯ÙØ§ Ø©ÙÙ ÙØ§Ø³ÙØ¥Ø§ Ø³Ø±Ø§Ø¯ÙÙ Ø§ÙÂ ÙÙØ¬Ø±Ø® ÙÙ ØÙÙØ°ÙÙ .Ø©ÙØµØ®Ø´ ÙÙÙÙØª ÙÙØ¹ ÙØ±Ø«Ø£Øª Ø§ÙÙ ÙÙÙÙ Ø©ÙÙØ®Ø§Ø¯ÙØ§ Ø©ÙÙ ÙØ§Ø³ÙØ¥Ø§ Ø³Ø±Ø§Ø¯ÙÙ Ø§ ÙØ¨Ù ÙÙ Ø¯Ù ØªØ¹ÙÙ Ø§ Ù Ø§Ø¸ÙÙØ§Â ÙÙÙØ£ ØÙÙØ±Ø®ÙØ¢Ø§ Ø©ÙÙØ®Ø§Ø¯ÙØ§ Ø©ÙÙ ÙØ§Ø³ÙØ¥Ø§ Ø³Ø±Ø§Ø¯ÙÙ Ø§ ÙÙÙØ¬Ø±ÙØ®Ø§ Ø¹Ù Ø©ÙØµØ®Ø´Ù Ø©ÙÙØªÙ Ø® ÙÙØ§ÙÙ Ø§ÙÙØ¯Ù Ø©ÙÙØ®Ø§Ø¯ÙØ§ Ø³Ø±Ø§Ø¯ÙÙ Ø§Â Ø£Ø²Ø¬ØªÙ ÙØ§ Ø§Ø¡Ø²Ø¬ ÙÙÙØªÙ Ø©ÙÙØ®Ø§Ø¯ Ø©Ø³Ø±Ø¯Ù ÙÙ ÙØ±Ø Ù ÙÙØ¹ØªÙØ§ .Ø³Ø±Ø¯ Ø«ÙØ Ø·ÙÙ Ø©ÙÙØ®Ø§Ø¯ Ø©Ø³Ø±Ø¯Ù ÙÙ ÙÙØ´Ù Ø±Ø«Ø£ØªÂ ÙÙ .Ø§ÙØ¨ Ø©ØµØ§ÙØ®Ø§ Ø©ÙÙ ÙÙØ¹ØªÙØ§ Ø¯Ø§ÙÙÙ Ø§ ÙÙ Ø¯ØØ§Ù ÙØ±Ø Ù ÙÙØ¹ØªÙØ§ ØØ¨ØµÙ ÙØ§ .Ø©ÙÙØ®Ø§Ø¯ÙØ§ Ø³Ø±Ø§Ø¯ÙÙ Ø§ ÙÙ Ù ÙÙØ¹ØªÙØ§ Ø©ÙÙÙ Ø¹ ÙÙ Â ØªÙÙÙÙ ØÙÙØ¨ÙÙØ§ ÙÙØ§Ø®ÙØ£Ø§Ù ÙÙÙØ¨ÙØ§ ÙÙÙÙØ§ ÙÙØ§Ø®ÙØ£Ø§ ÙØ£ ØÙÙÙØ³ÙØ§ Ø§ØµÙØµØ® ØµØÙØª ØªÙÙØ§ ÙÙØ¹ÙØ§ Ù ÙÙØ¹Øª ÙØ§ÙÙ Ø¹ÙØ§ÙÙØ§Â ÙÙÙØ³ÙØ§ Ø·Ø§ÙÙ Ø£Ù ÙØ±ÙÙØªÙØ§ Ø·Ø§ÙÙ Ø£ ÙÙÙØ´ØªÙ ØØ¨ÙØ§Ø·ÙØ§ Ø¹ÙØ³ÙØªÙ Ù Ø§Ø¹ Ù ÙÙØ¹Øª ÙÙ Ø§ÙÙ Ø¥Ù ØØ§Ø±Ø¬ Ù ÙÙÙ ØØ«ÙØ¯ÙØØ§ ØÙÙÙØ¹ØªÙØ§Ù.Ø¨ÙØ§Ø·ÙØ§ ÙØ¯Ù